Enabling precise predictions for left-right symmetry at colliders - Jonathan Kriewald; Miha Nemevšek; Fabrizio Nesti (European Physical Journal C: Particles and Fields)
Abstract We investigate the structure of the minimal left-right symmetric model that enables precise predictions in the gauge, scalar and neutrino sector. We revisit the complete set of mass spectra and mixings for the charged and neutral gauge bosons, would-be-Goldstones and gauge fixing, together with the ghost Lagrangian. In the scalar sector, we analytically re-derive all the massive states with mixings and devise a non-trivial physical input scheme, expressing the model couplings in terms of masses and mixing angles. Fermion couplings are also determined in closed form, including the Dirac mixing in the neutrino sector, evaluated explicitly using the Cayley–Hamilton theorem. These analytic developments are implemented in a comprehensive FeynRules model file. We calculate the one loop QCD corrections and provide a complete UFO file for NLO studies, demonstrated on relevant hadron-collider benchmarks. We provide various restricted variants of the model file with different gauges, massless states, neutrino hierarchies and parity violating $$g_L \ne g_R$$ g L ≠ g R gauge couplings.